FOOD CONSUMPTION OF MACRONUTRIENTS AND NUTRITIONAL STATUS OF PEOPLE WITH OSTOMY (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To evaluate the food intake of macronutrients and nutritional status of people with ostomy in the Amazonian context. Method: Quantitative cross-sectional study carried out in the specialized reference unit for people with ostomy, in the period from January to March 2020. The sample consisted of 77 people with ostomies, aged 21 to 88 years old, of both genders. We used sociodemographic information, clinical and behavioral aspects, anthropometric measurements and 24-hour recall. Statistical analysis was performed using BioEstat 5.0 and EpiInfo 3.5.1 software. Results: Most were male, aged between 35 and 50 years old. The most frequent types of ostomy were: colostomy (69%) and ileostomy (21%), with a temporary nature (43%), with neoplastic etiology in both sexes (60%). As for the nutritional status, most presented eutrophy according to the body mass index, but waist circumference showed increased metabolic risk in females, and the triceps skinfold thickness indicated excess adiposity in males (